Optical Properties on Bone Analysis: An Approach to Biomaterials - Andrea Antunes; José HL Pontes; Adamo F G Monte; Alcimar Barbosa; Nuno M F Ferreira (Proceedings, 2019)
The objective of the present study was to investigate the influence of demineralization solution on the optical properties of chicken femoral samples. Biomaterials based on bone have gained importance in clinical applications due to their properties as better osseointegration and biocompatibility. Biomateriais (bone substitute) are essentials to auxiliary in treatment of diseases related to bones such as bone density disorder, low bone mineral mass and the deterioration of bone tissue. Our data shows that integrating sphere technique permits to determinate significant difference in optical properties between healthy and demineralized samples. In this work, the optical properties of bone samples from chicken femur have been measured over the wavelength range 700−1000 nm.